TAYANGAN TELEVISI DAN SEPAK BOLA DI INDONESIA : TINJAUAN EKONOMI POLITIK MEDIA PADA PENYIARAN TELEVISI INDONESIA - Teddy Dyatmika (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
Football being the most watched by the people of Indonesia. The survey results show that the sport of football is the most favorite sport for the people of Indonesia. Many media impressions utilize football as a personal interest. Impressions many football commercialized through various kinds of advertising. Even the ads on football very disturbing impressions football lovers as they often appear during a match. Football lovers also have to spend money to be able to watch a football match favorite team because of a football game the category of big match only televised pay especially the Premier League. Football match in Indonesia are often infiltrated by political elements in propagandize the audience. The political elite exploit it for lovers of this sport very much and can provide benefits for them. Many of the political elite in Indonesia, which has the media so as to facilitate them in conveying political information in secret. Profits are also enjoyed by the owners of the cafe. For football lovers who do not have pay TV can utilize the cafe as a place to eat and enjoy a football game with their community.Key words: football, TV, Program, media, political economy, pay tv